Transfemoral trans-facial vein-superior ophthalmic vein to embolize cavernous sinus dural arteriovenous fistulas - Zhou, Zibo; Xu, Kan; Yu, Jinlu (Frontiers in Neurology, 2023)
Cavernous sinus dural arteriovenous fistula (CS-DAVF) is an abnormal communication between the CS and dural arteries from the internal carotid artery and external carotid artery. CS-DAVFs are not uncommon. The preferred treatment for most CS-DAVFs is transvenous embolization (TVE), which can achieve a high cure rate with few complications. The trans-inferior petrous sinus (IPS) route from the internal jugular vein to the CS is the favorite and most direct route to perform TVE in the great majority of CS-DAVFs. However, when the trans-IPS route fails and if the facial vein (FV) is patent and dilated, transfemoral trans-FV-superior ophthalmic vein (SOV) embolization of the CS-DAVF can be attempted. However, the transfemoral trans-FV-SOV route to embolize CS-DAVFs is often challenging, and there is insufficient knowledge about it. Therefore, an updated review of the transfemoral trans-FV-SOV route to embolize CS-DAVFs is necessary, and this review includes our experience. The images in this review are from our institute without the dispute of copyright. Issues regarding the transfemoral trans-FV-SOV route to embolize CS-DAV were discussed, including the FV anatomy and variation, various TVE routes to access CS-DAVF, the procedure of the transfemoral trans-FV-SOV route to embolize CS-DAVF, difficulty, and solution of the transfemoral trans-FV-SOV route to embolize CS-DAVF, and complications and prognosis of transfemoral trans-FV-SOV to embolize CS-DAVF. By reviewing the transfemoral trans-FV-SOV route to embolize CS-DAVFs, we found that this route provides a valuable alternative to the other transvenous routes. A good prognosis can be obtained with the transfemoral trans-FV-SOV route to embolize CS-DAVFs in select cases.